Cross-Cultural Validation Study of the Japanese Version of the ABILOCO-Kids in Ambulatory Children With Cerebral Palsy Using Rasch Analysis. (2nd November 2019) - Himuro, Nobuaki; Nishibu, Hisato; Abe, Hirokazu; Mori, Mitsuru
Abstract: Aims : To determine the structural validity, construct validity, cross-cultural validity, internal consistency and test–retest reliability of the Japanese version of the ABILOCO-Kids in children with cerebral palsy. Methods : One-hundred sixteen parents of children with cerebral palsy (Gross Motor Function Classification System level I [ n = 66], II [ n = 32], and III [ n = 18]) reported on walking ability using the Japanese version of the ABILOCO-Kids. For test–retest reliability, 23 participants were evaluated. Results : The mean ABILOCO-Kids logit score was 2.48 (range –7.44 to 5.83). Rasch analysis and principal component analysis were used to determine the structural validity. The construct validity was confirmed on the basis of differences in the ABILOCO-Kids scores among the Gross Motor Function Classification System levels. Cronbach's α and the item-to-total correlation coefficient supported the internal consistency. The intra-class correlation coefficient was 0.96, standard error of measurement 0.56 and minimal detectable change 1.55. The cross-cultural validity analyses showed differential item functioning according to the analyses of the invariance of item difficulty and person's ability estimates. Conclusions : The ABILOCO-Kids is a reliable and valid measure of walking ability in children with cerebral palsy in Japan. The lack of evidence on cross-cultural validity indicates we should interpret results cautiously in cases of international comparison.